2017
DOI: 10.1017/qua.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Cosmogenic nuclide age estimate for Laurentide Ice Sheet recession from the terminal moraine, New Jersey, USA, and constraints on latest Pleistocene ice sheet history

Abstract: The time at which the Laurentide Ice Sheet reached its maximum extent and subsequently retreated from its terminal moraine in New Jersey has been constrained by bracketing radiocarbon ages on preglacial and postglacial sediments. Here, we present measurements of in situ produced 10Be and 26Al in 16 quartz-bearing samples collected from bedrock outcrops and glacial erratics just north of the terminal moraine in north-central New Jersey; as such, our ages represent a minimum limit on the timing of ice recession … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 94 publications
(170 reference statements)
2
37
0
Order By: Relevance
“…At the LGM, the southeastern margin of the LIS extended into the Gulf of Maine ~600 km beyond the present coastline and onto Georges Bank (Pratt and Schlee, 1969;. Cosmogenic exposure dating indicates that the LIS margin initially pulled back from its maximum extent in southeastern Massachusetts at Martha's Vineyard, dated to 27.5 ± 1.6 ka (n = 8), and northern New Jersey, dated to 25.2 ± 1.3 ka (n = 16; Corbett et al, 2017; these ages and all those reported below are recalculated using the northeastern North American production rate from Balco et al (2009) and give uncertainties as the standard error of boulder ages and the production rate uncertainty (4.8%), added in quadrature). Several recessional moraines in southernmost New…”
Section: Paleoclimate Context and New England Deglaciationmentioning
confidence: 99%
“…At the LGM, the southeastern margin of the LIS extended into the Gulf of Maine ~600 km beyond the present coastline and onto Georges Bank (Pratt and Schlee, 1969;. Cosmogenic exposure dating indicates that the LIS margin initially pulled back from its maximum extent in southeastern Massachusetts at Martha's Vineyard, dated to 27.5 ± 1.6 ka (n = 8), and northern New Jersey, dated to 25.2 ± 1.3 ka (n = 16; Corbett et al, 2017; these ages and all those reported below are recalculated using the northeastern North American production rate from Balco et al (2009) and give uncertainties as the standard error of boulder ages and the production rate uncertainty (4.8%), added in quadrature). Several recessional moraines in southernmost New…”
Section: Paleoclimate Context and New England Deglaciationmentioning
confidence: 99%
“…Dyke et al, 2004), glacial varves , and cosmogenic nuclide dating (Balco et al, 2002;Balco and Schaefer, 2006;Bierman et al, 2015;Davis et al, 2015;Corbett et al, 2017;Koester et al, 2017;Hall et al, 2017;Fig. 4).…”
Section: Ice Extentmentioning
confidence: 99%
“…Dyke et al, 2004), glacial varves (Ridge, 2004;Ridge et al, 2012), and cosmogenic nuclide dating (Balco et al, 2002;Balco and Schaefer, 2006;Bierman et al, 2015;Bromley et al, 2015;Davis et al, 2015;Corbett et al, 2017;Koester et al, 2017;Hall et al, 2017;Fig. 4).…”
Section: Ice Extentmentioning
confidence: 99%